Peningkatan Literasi Digital Melalui Edukasi Pemanfaatan Artificial Intelligence (AI) pada Siswa SMPN 2 Bogor: Pengabdian - Shulhuly Ashfahani; Tri Yulistyarani; Yuli Purnamasari; Azizah Sholy Fauziah; Ika Nuraini Natalia Zai; Muhammad Haikal Fadilah; Rizki Buli Akbar; Syavalia Deviani Suseno (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This community service activity aims to improve students’ understanding of the wise use of Artificial Intelligence (AI) from an early age. The background of this program is the high level of AI usage among students, which is not yet accompanied by adequate understanding of its concepts, benefits, and potential risks. The method used was an educative-participatory approach through interactive counseling involving lecturers, students, and active participation from participants. The activity was conducted at SMPN 2 Bogor, targeting 32 seventh-grade students. The materials covered basic concepts of AI, how it works, its benefits and risks, as well as ethical considerations in its use. The results showed an increase in students’ knowledge, indicated by a 4.33% improvement in the average score from pre-test to post-test. In addition, students demonstrated high enthusiasm and active engagement throughout the activity. Therefore, this program contributes to enhancing students’ understanding and encouraging responsible and wise use of AI.